Implementation of two Distinct Plant Species in a Constructed Wetland System for Domestic Wastewater Treatment - Quang Sang Huynh; Thuong Minh Huynh Truong; My Linh Nguyen (Journal of Technical Education Science, 2025)
This study illustrates the efficacy of vertical flow-constructed wetlands (VFCWs) systems as a sustainable and ecologically sound approach for the treatment of domestic wastewater. The implementation of the VFCWs system demonstrated a high level of efficacy in the removal of organic matter (COD), ammonium (N-NH4+), and phosphate (P-PO43-) from wastewater. The research utilized two plant species, namely Azolla pinnata (A. pinnata) and Echinoderms amazonicus (E. amazonicus), both of which exhibited remarkable capabilities in removing pollutants. The COD, N-NH4+ and P-PO43- removal efficiency of A. pinnata was found to be 87.6%, 89.7%, 89.7%, respectively. Meanwhile, E. amazonicus demonstrated removal efficiencies of 72.6% for COD, 79.7% for N-NH4+, and 90.0% for P-PO43-. Meanwhile, E. amazonicus demonstrated removal efficiencies of 72.6% for COD, 79.7% for N-NH4+, and 90.0% for P-PO43-. The results of this study indicated that both plant species could effectively treat domestic wastewater. In addition, it should be noted that the VFCWs system is very much below the QCVN 14:2015/BTNMT – Vietnamese National Standard for water quality discharge standards. This process guarantees that the wastewater that has undergone treatment adheres to the prescribed regulatory thresholds for pollutant concentration. The utilization of VFCWs in small and medium-sized wastewater treatment facilities can therefore be considered a financially viable and highly effective approach for the removal of pollutants.